Estilos parentales y logros de aprendizaje en el área de comunicación en estudiantes del quinto grado de primaria de la Institución Educativa Claverito, Iquitos 2023 - Oliveira Becerra, Willian (2024)
This research, with a quantitative approach, sought to identify the relationship between parenting styles and learning achievements in the area of communication of fifth grade primary school students at the Claverito Educational Institution, Iquitos, during the 2023 school year. Questionnaires were applied to a sample of 152 students, and the analysis was carried out using Spearman's correlation coefficient. The results showed a significant and positive correlation (r=0.762, p=0.000) between parenting styles and learning achievements. 74.5% of parents showed an authoritarian style, 15.6% a democratic style, and 9.9% a permissive one. It is concluded that promoting the democratic style and improving communication between parents and children could increase learning achievements in the institution.